Caminhar e desenhar : indicador de qualidade através da percepção - Maia, Hortênsia Gadelha (2022)
The present research is based on the theme of the identification of instruments for reading the urban landscape. In this sense, a model of urban analysis is suggested that systematizes ways of identifying spatial characteristics that indicate quality present in public open spaces, such as sidewalks and squares. The morphology and organization of these spaces suggest social relationships that infer affectivity. Thus, the presence of quality indicators in public space, being social and morphological, can quantify a level of spatial quality. The morphological analysis has as bibliographic and technical support theories of authors, such as Hillier and Hanson (1989), Marcus (2007), Kevin Lynch (2011, 2015) and Gordon Cullen (2008), bringing a different association of analysis tools and methodologies urban development through information modeling. Through the drawings collected in graphic journals, we seek a more attentive perception of urban poetry, such a tool is studied by Salavisa (2008), Brasil (2018) and Rodrigues (2016). As a result of the investigation, a classification of walking spaces was elaborated that reflects the nuances present in the spatial form studied and that refer to life in these places. A translation of perception into quantifiable indicators was arrived at, through an analysis of space that relates sensitive aspects of human perception and the abstract-formal approach, bringing together the phenomenological and the logical.